Determinants of Childhood Obesity in Representative Sample of Children in North East of Iran. (15th July 2012) - Baygi, Fereshteh; Dorosty, Ahmad Reza; Kelishadi, Roya; Qorbani, Mostafa; Asayesh, Hamid; Mansourian, Morteza; Mirkarimi, Kamal
Abstract : Childhood obesity has become, a global public health problem, and epidemiological studies are important to identify its determinants in different populations. This study aimed to investigate factors associated with obesity in a representative sample of children in Neishabour, Iran. This study was conducted among 1500 randomly selected 6–12-year-old students from urban areas of Neishabour, northeast of Iran. Then, through a case-control study, 114 obese (BMI ≥ 95 th percentile of Iranian reference) children were selected as the case group and were compared with 102 controls (15 th ≤ BMI < 85 th percentile). Factors suggested to be associated with weight status were investigated, for example, parental obesity, child physical activity levels, socio-economic status (SES), and so forth. The analysis was conducted using univariate and multivariate logistic regression (MLR) in SPSS version 16. In univariate logistic regression model, birth weight, birth order, family extension, TV watching, sleep duration, physical activity, parents' job, parents' education, parental obesity history, and SES were significantly associated with children's obesity. After MLR analysis, physical activity and parental obesity history remained statistically significant in the model. Our findings showed that physical activity and parental obesity history are the most important determinants for childhood obesity in our population. This finding should be considered in implementation of preventive interventions.